ENHANCING STUDENTS’ ANALYTICAL EXPOSITION WRITING THROUGH COLLABORATIVE WRITING STRATEGY: AN EXPERIMENTAL STUDY AT MAN 3 PADANG - Wahyuni Lidya Putri; Muhammad Al Hafizh (English Review: Journal of English Education, 2025)
This study examines the effect of Collaborative Writing Strategy (CWS) on students' writing skills, particularly in composing analytical exposition texts. Conducted at MAN 3 Padang, the study involved two eleventh grade classes, XI IPA 3 and XI IPA 4, using an experimental design. The experimental group received instruction through CWS, while the control group was taught using conventional teacher-centered methods. Data were collected using pre-tests and post-tests and analyzed to determine improvements in writing performance. The study findings revealed that the implementation of CWS significantly improved students' writing skills compared to the traditional method. The improvements were observed across different levels of student motivation, indicating that CWS is an inclusive and effective teaching approach. This study highlights the pedagogical potential of collaborative learning strategies in improving academic writing skills, especially in an EFL context. The results advocate the integration of CWS into writing instruction to foster student engagement, peer interaction, and equitable learning outcomes regardless of motivational differences.